New Drug Delivery Systems in Livestock Animals - Herdiana, Yedi (Indonesian Journal of Pharmaceutics, 2024)
The development of animal husbandry in Indonesia has seen positive progress through government initiatives to increase productivity and efficiency. The field of veterinary medicine plays a vital role in maintaining the health and productivity of livestock, which ultimately impacts the productivity and quality of animal products. However, areas still require improvement, particularly infrastructure, technology, and management. Pharmaceutical science, specifically veterinary pharmacy, focuses on treating animals using different drug delivery systems due to physiological differences. Significant modification in livestock drug delivery involves adjusting medication based on animal needs to improve health and reduce the risk of overmedication and antibiotic resistance. Advancements in technology and medical developments are continuously being reviewed and studied to improve veterinary medicine.